Pouvoir d’agir, en analyse de l’activité - Gaspard Brun (Activités)
There is an inflation in the uses of the French expression “pouvoir d’agir” which presents certain affinities with the concept of “empowerment”. The aim of this article is to confront the different ways of using this expression in certain activity analysis theories. We will attempt to explore the philosophical foundations of this terminology, essentially from a Spinozist perspective. It is for this reason that we will analyse the expression as it is used in the writings of Spinoza himself, so as to propose a new comprehension of the framework of clinical activity and activity theories. Our theorical framework is philosophical for conceptual analysis and ergological for activity analysis.